Sources of the small firm financing premium: Evidence from euro area banks - Sarah Holton; Fergal McCann (European Central Bank (ECB), 2017)
The post-2008 period in the euro area was characterised by sharp dispersion in borrowing costs faced by firms, across both countries and firm types. This dispersion was an important manifestation of the financial fragmentation" which hampered the smooth transmission of accommodative monetary policy. Using bank level data from 2007 to 2015, we directly measure the borrowing cost dispersion across firm types by calculating the difference in the interest rate charged by the same bank in the same month for loans to small and large firms (the "Small Firm Financing Premium", SFFP). We assess the role played by both bank and macroeconomic factors in explaining the variation in the SFFP across countries and through time. We provide evidence that bank market power, sovereign bond holdings and balance sheet weaknesses led to disproportionate borrowing cost increases for small firms, and exacerbated the impact of a weak macroeconomy during this period.
Keywords: G20; G21; E51; 330; SMEs; cost of credit; bank balance sheets; bank market power